Using of behavioural tests on two-year-old thoroughbreds - Szabó, Szilvia; Tóthné Maros, Katalin (Animal welfare, Ethology and Housing Systems (AWETH), 2006)
The aim of this present study was to use simple behavioural tests, in this case novel object and open field examinations, on horses of standard age and housing conditions, to identify whether there are any typical behavioural tendencies according to their sex. The objective was to confirm that these tests give reliable results, which may be applied in general stud management. The research was carried out at Bábolna National Stud Thoroughbred Yard of Dióspuszta. All together 14 two-year-old thoroughbreds took part in the analysis (7 stallions and 7 mares), and tests were repeated on two occasions. The study affirmed that simple behavioural tests – when used in combination – give valuable information regarding the behaviour of young thoroughbreds, and can highlight any definitive differences. The reactions of mares to social isolation in open field tests was found more distinct (i.e. animals were more sensitive) than that of stallions, while the novel object test did not show any difference between sexes. Moreover, results showed that combined behavioural variables indicate relative stable behavioural reactions in time. It was confirmed that especially open field tests are able to classify typical behavioural tendencies of horses according to their sex. In conclusion, the study confirmed that simple behavioural tests are valid methods to study typical behavioural tendencies of thoroughbred horses. In addition, it was also found that their application in general stud management facilitates a better understanding of sex differences in handling and housing needs.